Randomized controlled trial of once-per-week intermittent fasting for health improvement: the WONDERFUL trial. Issue 2 (3rd September 2021) - Bartholomew, Ciera L; Muhlestein, Joseph B; May, Heidi T; Le, Viet T; Galenko, Oxana; Garrett, Kelly Davis; Brunker, Cherie; Hopkins, Ramona O; Carlquist, John F; Knowlton, Kirk U; Anderson, Jeffrey L; Bailey, Bruce W; et al.
Abstract: Aims: Low-density lipoprotein cholesterol (LDL-C) predicts heart disease onset and may be reduced by intermittent fasting. Some studies, though, reported that fasting increased LDL-C; however, no study evaluated LDL-C as the primary endpoint. This randomized controlled trial evaluated the effect of low-frequency intermittent fasting on LDL-C and other biomarkers. Methods and results: Adults aged 21–70 years were enrolled who were not taking a statin, had modestly elevated LDL-C, had ≥1 metabolic syndrome feature or type 2 diabetes, and were not taking anti-diabetic medication ( N = 103). Water-only 24-h fasting was performed twice weekly for 4 weeks and then once weekly for 22 weeks; controls ate ad libitum . The primary outcome was 26-week LDL-C change score. Secondary outcomes (requiring P ≤ 0.01) were 26-week changes in homeostatic model assessment of insulin resistance (HOMA-IR), Metabolic Syndrome Score (MSS), brain-derived neurotrophic factor (BDNF), and MicroCog general cognitive proficiency index (GCPi). Intermittent fasting ( n = 50) and control ( n = 53) subjects were, respectively, aged 49.3 ± 12.0 and 47.0 ± 9.8 years, predominantly female (66.0% and 67.9%), and overweight (103 ± 24 and 100 ± 21 kg) and had modest LDL-C elevation (124 ± 19 and 128 ± 20 mg/dL). Drop-outs ( n = 12 fasting, n = 20 control) provided an evaluable sample of n = 71 ( n = 38 fasting, n = 33 control). Intermittent fasting did not change LDL-C (0.2 ± 16.7 mg/dL) vs. control (2.5 ± 19.4 mg/dL; P = 0.59), but it improved HOMA-IR (−0.75 ± 0.79 vs. −0.10 ± 1.06; P = 0.004) and MSS (−0.34 ± 4.72 vs. 0.31 ± 1.98, P = 0.006). BDNF ( P = 0.58), GCPi ( P = 0.17), and weight (−1.7 ± 4.7 kg vs. 0.2 ± 3.5 kg, P = 0.06) were unchanged. Conclusions: A low-frequency intermittent fasting regimen did not reduce LDL-C or improve cognitive function but significantly reduced both HOMA-IR and MSS. Trial registration:  clinicaltrials.gov, NCT02770313. Graphical Abstract: